Differences in Metabolite Profiles and Bioactivities of Intra-Strain Variants of Marine Fungus Penicillium antarcticum KMM 4668 - Gleb V. Borkunov; Natalya N. Kirichuk; Viktoria E. Chausova; Roman S. Popov; Olesya I. Zhuravleva; Ekaterina A. Chingizova; Ekaterina A. Yurchenko; Marina P. Isaeva; Anton N. Yurchenko (Metabolites)
Background: During the cultivation of the marine fungus KMM 4668 on solid agar medium, the morphological instability of the strain was observed. As a result of the selection work, five intra-strain variants, named KMM 4711, KMM 4712, KMM 4713, KMM 4714, and KMM 4715, were obtained. Methods: The main objectives of this work were to compare the parent strain and its intra-strain variants using multi-locus phylogenetic analysis and to study the UPLC MS metabolite profiles and cytotoxic activities of their extracts. Results: A study of the original strain, KMM 4668, and its intra-strain variants using multi-locus phylogenetic analysis showed that they are sequence identical and belong to Penicillium antarcticum. UPLC MS metabolite profiling of fungal extracts revealed 20 compounds, including cladosporin-related polyketides, carotane sesquiterpenoids, andrastine meroterpenoids, and alkaloids. It was shown that the intra-strain variants KMM 4713 and KMM 4714 differed most strongly from the others in the increased production of cladosporin-related compounds, carotanoids, and the alkaloid chrysogin. In addition, the influence of fungal extracts on the viability of four mammalian cell lines was investigated. Conclusions: It has been shown that the intra-strain variants of P. antarcticum KMM 4668 may be promising sources of bioactive secondary metabolites.